The Contested Commons: The Failure of EU Fisheries Policy and Governance in the Mediterranean and the Crisis Enveloping the Small-Scale Fisheries of Malta - Said, Alicia; Tzanopoulos, Joseph; MacMillan, Douglas (Frontiers in Marine Science, 2018)
This paper highlights how multi-scalar interstitial policy failings of the EU fisheries policy can directly trigger policy gaps in fisheries management at the expense of artisanal communities, leading to further expansion opportunities for industrial fishing and triggering instability and marginalisation of traditional fishing communities. In order to contextualize and demonstrate this complexity, we explore a detailed scenario of the Maltese waters to show how the development of a national policy portfolio post-EU accession has destabilized long-existing functional fishing governance mechanisms and now pose a direct challenge to the sustainable management of the marine socio-ecological system. Using a mixed-method approach to investigate the partially obscured social, economic and political dynamics which drive marine policy, we demonstrate how the coastal fisheries have become subject to multiple-use competition arising primarily from a burgeoning recreational fishing sector that has benefited from ‘access-enabling policies’, and is, to a great extent uninhibited by fish conservation regulations. Our findings demonstrate how a deeper understanding of the socio-political ramifications of policy processes is necessary to improve the governance and management of contested and congested open-access fisheries.